Long-term survival in AIDS-related primary central nervous system lymphoma. Issue 1 (30th August 2016) - Gupta, Neel K.; Nolan, Amber; Omuro, Antonio; Reid, Erin G.; Wang, Chia-Ching; Mannis, Gabriel; Jaglal, Michael; Chavez, Julio C.; Rubinstein, Paul G.; Griffin, Ann; Abrams, Donald I.; Hwang, Jimmy; et al.
Abstract: Background: The optimal therapeutic approach for patients with AIDS-related primary central nervous system lymphoma (AR-PCNSL) remains undefined. While its incidence declined substantially with combination antiretroviral therapy (cART), AR-PCNSL remains a highly aggressive neoplasm for which whole brain radiotherapy (WBRT) is considered a standard first-line intervention. Methods: To identify therapy-related factors associated with favorable survival, we first retrospectively analyzed outcomes of AR-PCNSL patients treated at San Francisco General Hospital, a public hospital with a long history of dedicated care for patients with HIV and AIDS-related malignancies. Results were validated in a retrospective, multicenter analysis that evaluated all newly diagnosed patients with AR-PCNSL treated with cART plus high-dose methotrexate (HD-MTX). Results: We provide evidence that CD4+ reconstitution with cART administered during HD-MTX correlates with long-term survival among patients with CD4 <100. This was confirmed in a multicenter analysis which demonstrated that integration of cART regimens with HD-MTX was generally well tolerated and resulted in longer progression-free survival than other treatments. No profound differences in immunophenotype were identified in an analysis of AR-PCNSL tumors that arose in the pre- versus post-cART eras. However, we detected evidence for a demographic shift, as the proportion of minority patients with AR-PCNSL increased since advent of cART. Conclusion: Long-term disease-free survival can be achieved in AR-PCNSL, even among those with histories of opportunistic infections, limited access to health care, and medical non-adherence. Given this, as well as the long-term toxicities of WBRT, we recommend that integration of cART plus first-line HD-MTX be considered for all patients with AR-PCNSL.